The Use of Exercise and Dietary Supplements Among British Soldiers in Afghanistan. Issue 3 (1st September 2011) - Boos, Christopher; Simms, P; Morris, F R; Fertout, M
Abstract : Background and Objectives: Recently published case reports, coupled with a large observational study of 1017 deployed servicemen to Iraq (January 2009), has highlighted the issue and potential concerns regarding the unregulated use of dietary and exercise supplements within the British military. Consequently, an exploratory pilot study was undertaken to assess whether the findings of the previous Iraq study were applicable to current deployed British servicemen in Afghanistan. Methods: This was a voluntary questionnaire-based study targeted at individuals attending a health promotion fair in Camp Bastion, Afghanistan in June 2010. Results: From 150 questionnaires handed out there were 87 completed questionnaires (58% return). The mean age was 28.0 (SD 7.1; range of 18-50 years) with 89.7% being male. From the total of 87 persons 46.0% were self-declared current smokers with 37.9% admitting to drinking > 6 caffeinated drinks per day. Forty nine persons (56.3%) admitted to a history of supplement use with 35 (40.2% compared with 32.0% in 2009 in Iraq) declaring current use. The average duration of supplement use among current users was 3.0 (2.0-9.0) months. The main sources of supplement supply were via local NAAFI purchase (57.1%), internet purchase (40.0%) and via their local chemist (2.9%). The main types of supplement used were proteins / amino acids (85.7%), creatine (34.3%), chromium (31.4%), stimulants (17.1%), hydroxycut (5.7 %), and testosterone boosters (1.2%) with no persons admitting to the use of ephedra or anabolic steroids. Conclusions: A significant proportion of the British servicemen employed on operations in Afghanistan who were sampled, admitted to current dietary and exercise supplement use whilst on deployment. The results of this small study suggest that their use on operations may be increasing. Smoking rates and caffeine consumption, on deployment, remain high in the British military. A larger detailed study with greater representation among soldiers deployed to forward operating bases would be helpful to fully appreciate the scale of supplement use.